STUDI KOMPARASI KESIAPAN PEMBELAJARAN AKUNTANSI KEUANGAN DI UNIVERSITAS SURABAYA DAN STIE PERBANAS SURABAYA DALAM RANGKA ADOPSI IFRS: PERSPEKTIF AKADEMISI - Jessica Irma Wijaya; Yie Ke Feliana (Akuntansi dan Teknologi Informasi, 2021)
The focus of this study is how learning process about IFRS in accounting curriculum Universitas Surabaya and STIE Perbanas Surabaya using qualitative research paradigm. Interviews, observations, and documentary analysis were used during data collection processes. The result of this study is the curriculum of accounting educationof Universitas Surabaya and STIE Perbanas Surabaya have been updated with IFRS. The accounting lecturers of these universities never facing any significant difficulty in adjusting the accounting education curriculum because so many training, seminar, or socialization about IFRS have been participated. Learning methods and support from institutions become evaluation in the current process of accounting education. The learning methods for accounting students of Universitas Surabaya and STIE Perbanas Surabaya have no significant difference although they use different approaches. In term of the support of institutions, Universitas Surabaya is better than STIE Perbanas Surabaya.